BMI Home Workout: Exercise Application Without Any Equipment Along with BMI Calculations - Anis Syazwani Ahmad Komari,; Muhammad Azam Akhram Abdullah,; Putera Syaqrizal Hafizan M. Afzalizan, (Multidisciplinary Applied Research and Innovation, 2023)
Due to the spread of the covid-19 virus, all communities are instructed to stay at home and cannot go out to the park or gym to do exercise activities. This is not a reason for us not to exercise even if we do not have complete equipment. Therefore, this application was developed to help them stay active even at home. A BMI home workout application can be a valuable tool to help you stay calm and continue to protect your health over the years. It provides four types of workouts and takes less than five minutes for each exercise pleasure, even at home, without special equipment, and with limited space. The BMI Home workout application has been developed for Android devices. This application helps people maintain the health and fitness of their bodies. This application is suitable for any range of age especially for those who care about the health of the body. According to the ADDIE model, which has five phases namely analysis, design, development, implementation, and evaluation phases, this application is developed using unity software. In this era, society is very concerned about a beautiful body shape, therefore a balanced diet and exercise routine are very important. With this application, we can know which BMI category we belong to. We can also learn about the food pyramid and Developed for Android devices Also, we can exercise at home. And most importantly does not require exercise equipment. The application is simple and cost-free. The result of this project is expected that the BMI Home Workout application can be used by an android user and a user-friendly that can be used by every range of age. BMI Home Workout application contains appropriate workouts at home and calculates the Body Mass Index (BMI). Lastly, we hope this application can upgraded further by produce more of the latest features that users need, such as collecting healthy food recipe videos and users' overview of their fitness activities by day, week, month, or another time period. It helps evaluate the progress in a given period of time and set long-term goals accordingly.